Peran UI/UX Pada Layanan Aplikasi Mytelkomsel Terhadap Keputusan Pembelian dan Loyalitas Pelanggan - Novenya Rahmadani; Siti Ning Fardida (BADAN PENERBIT STIEPARI PRESS, 2024)
The crucial role of good UI/UX design in a business environment is examined in this article for several reasons. Well-designed user interfaces and user experiences (UI/UX) can increase user satisfaction by making the interaction process simple and entertaining. Companies can also increase conversion rates. Moreover, a pleasant user experience lowers development and support expenses and increases customer loyalty. Excellent UI/UX design also helps a company stand out from the competition and improves its reputation. Investing in UI/UX is a strategic move that is essential to gaining and retaining a competitive edge in a competitive company climate. Specifically regarding the MyTelkomsel application, the research was conducted qualitatively using Qualitative and unstructured observation methods on aspects of the MyTelkomsel application. Specifically regarding the MyTelkomsel application, the research was conducted qualitatively using unstructured observation methods on the digital aspects of the MyTelkomsel application, which has been downloaded by more than 50 million users in Indonesia. Many MyTelkomsel users still complain about difficulties in using the application, which can result in decreased customer loyalty in subscribing to Telkomsel cards. Based on the research results, the conclusion that can be drawn is that positive user interfaces and user experiences (UI/UX) influence customer loyalty.